Preparation of ZnO/Cetyl Trimethyl Ammonium Salt/Hectorite as Catalyst in Alizarin Red S Photo-oxidation - Fatimah, Is (Asian Journal of Chemistry, 2011)
Preparation of zinc oxide immobilized in cetyl trimethyl ammonium-intercalated hectorite (ZnO/ CTMA/Hec) and its photocatalytic study for alizarin red S (ARS) photo-oxidation has been conducted. The synthesis of ZnO/CTMA/Hec catalyst was performed by pre-intercalation process toward synthetic hectorite followed by dispersion of ZnO via pillarization process. Catalyst characterization performed by XRD, surface area analyzer and energy dispersive X-ray (EDX). Activity test of material as photocatalyst in alizarin red S photo-oxidation focused on its evaluation in the alizarin red S degradation rate compared with hectorite and bulk-ZnO. The result showed that ZnO/CTMA/Hec preparation affect significantly to increase photoactivity compared to raw support; hectorite. The increase in activity was ensured from the linear correlation between catalyst dosage to the degradation rate.